Reinterpretasi Hak Waris Perempuan dalam Islam: Sebuah Kajian Qs. Al-Nisā'/4: 11 - Suhra, Sarifa; Kallang, Abdul; Misdah (Al-Ulum, 2023)
One of the problems that arise after death is regarding the distribution of property to whom and how much share will be obtained, this has been regulated in Islamic inheritance law, but an issue that until now is often debated and prone to conflict in the family is the inheritance rights of women who in the Islamic inheritance system are different from men so that there is a stigma that Islamic inheritance law tends to be discriminatory and gender biased, This is due to the assumption that the inheritance system in Islam is something patent and cannot be changed, whereas the formulation of inheritance in the books of fiqh is the interpretation of scholars in the social setting where the ulama live, therefore it is necessary to reinterpret the inheritance system for women because the law is actually a social response that will continue to interact with the social construction of community life.